Peran Guru Dalam Meningkatkan Kedisplinan Siswa Kelas IV Di SD 1 Gribig Kudus - Nur Fajrie; Kinesti Destia Syafitri; Mareta Wahyu Nur Hanifah; Lela Ayu Septyani (CV. ITTC INDONESIA, 2023)
This study aims to analyze the teacher's role in improving the discipline of fourth grade students at SD 1 Gribig. This research was conducted using qualitative methods. Data was collected through classroom observations, interviews with teachers, and analysis of documents related to school policies and teaching practices. The research participants included fourth grade teachers and fourth grade students at SD 1 Gribig. The results of the study show that teachers have a significant role in improving student discipline. The teacher acts as a teacher, educator, and mentor who provides clear examples and expectations regarding disciplinary behavior. Teachers are also responsible for creating a conducive learning environment and managing discipline in the classroom. They involve students in setting class rules, provide consistent rewards and sanctions, and provide individual guidance when needed. Obstacles faced by teachers in improving student discipline include lack of attention from students to rules, differences in the level of discipline between students, and lack of support from the environment outside the school. In conclusion, the teacher's role in improving the discipline of fourth grade students at SD 1 Gribig is very important. Teachers have the responsibility to shape student discipline behavior through teaching, mentoring, and setting a conducive learning environment. In facing obstacles, teachers need to use appropriate strategies and collaborations to achieve the goal of increasing student discipline.